Optimization of Drying Conditions of Chlorella vulgaris Using Tray Dryer for Biodiesel Feedstock - Lidya Elizabeth; Rispiandi; Laily Isna Ramadhani; Dhyna Analyes Trirahayu; Hidayatulloh, Irwan (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Microalgae are one of the primary feedstocks for biodiesel production due to their high lipid content, ranging from 4–77% of dry weight. Chlorella vulgaris is considered a superior species with a lipid content of 5–40% based on dry weight. Drying microalgae into powder form has been developed to improve handling, storage, and application, including in biodiesel production. However, drying remains a major challenge, as inappropriate methods may cause lipid degradation due to high-temperature exposure. This study aims to dry Chlorella vulgaris using a tray dryer and to optimize its operating conditions through analysis of variance based on Response Surface Methodology (RSM). Based on the literature, no previous studies have used a tray dryer for drying Chlorella vulgaris. Optimization was conducted by varying drying temperature (55–75°C) and air velocity (1.5–1.7 m/s) to achieve the highest drying efficiency. The highest efficiency was achieved at 79°C and 1.6 m/s, reaching 99.99% with energy consumption of 603.17 kWh/kg. Meanwhile, RSM analysis showed that the optimum condition was at 75°C and 1.7 m/s, resulting in 99.89% efficiency with energy consumption of 693.97 kWh/kg. Drying at both 75°C and 79°C proved to be efficient and safe in preserving lipid compounds in microalgae.